Architectural Science and the Sun : The poetics and pragmatics of solar design - Fajkus, Matt; Whitsett, Dason (London : Taylor and Francis, 2018)
"Architectural Science and the Sun synthesizes physics, climate, program, and perception to provide a foundation in the principles of architectural science related to the sun: solar geometry, solar analysis and design techniques, passive design principles, and daylighting. Part analytical handbook, part inspiration source for schematic design, the content comprises a critical component of effective sustainable design.Beyond the purely technical aspects of these topics, Architectural Science and the Sun begins with the premise that great architecture goes beyond energy performance and the visual-aesthetic to engage all of the senses. Given that the stimuli to which our senses respond are physical phenomena such as light, heat, and sound, the designer must manipulate these parameters through the craft of building form and technology to create the desired qualitative experience. This book is designed to help the reader develop that skill."--Provided by publisher.
Chapter 1 Introduction / Matt Fajkus Dason Whitsett -- chapter 2 The Earth-Sun Relationship / Matt Fajkus Dason Whitsett -- chapter 3 The Geocentric Model / Matt Fajkus Dason Whitsett -- chapter 4 Climate and Solar Radiation / Matt Fajkus Dason Whitsett -- chapter 5 The Sun and Form / Matt Fajkus Dason Whitsett -- chapter 6 Received Shadows / Matt Fajkus Dason Whitsett -- chapter 7 The Solar Microclimate / Matt Fajkus Dason Whitsett -- chapter 8 Creating Shadows / Matt Fajkus Dason Whitsett -- chapter 9 Fenestration and the Sun / Matt Fajkus Dason Whitsett -- chapter 10 Light and Effect / Matt Fajkus Dason Whitsett.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture and solar radiation